Identifikasi Polerovirus Penyebab Klorosis pada Cabai Asal Bali, Indonesia - Rita Kurnia Apindiati; Gede Suastika; Kikin Hamzah Mutaqin (Jurnal Fitopatologi Indonesia, 2015)
Based on the results of a survey conducted on chilipepper plants in Kertha Village, Payangan Subdistrict, Gianyar District, Bali Province, many chilipepper plants with chlorosis symptoms caused by the virus was observed. Infected plants showed yellowing of the lamina, but the veins remain green. Identification was focused on the Pepper vein yellows virus (PeVYV) through transmission using Aphis nasturtii, observation on the morphology of virus particles, total RNA detection by reverse transcription-polymerase chain reaction (RT-PCR), and nucleotide sequence. The results showed that the disease can be transmitted from infected plant to healthy plant using A. nasturtii. Viral particle has hexagonal shape with the diameter ~30 nm. RT-PCR of total RNA from severe, moderate, and mild symptomatic infected plants, using specific primer sets for coat protein gene of PeVYV successfully amplified DNA with size of ~650 bp. Coat protein gene sequence of PeVYV isolates Bali, Indonesia showing different chlorosis intensity had the highest homology with PeVYV isolates from Taiwan 95.1–96.6%. Based on the data, PeVYV has been confirmed as the cause of chlorosis in chilipepper plants in Bali, Indonesia.